2018
DOI: 10.4238/gmr16039908
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Sub-lethal doses of neonicotinoid and carbamate insecticides reduce the lifespan and alter the expression of immune health and detoxification related genes of honey bees (Apis mellifera)

Abstract: Honey bees (Apis mellifera) are exposed to sublethal doses of insecticides, but little is known about insecticide effects on their survivorship associated to health-related gene expression. To test the effect of sublethal doses of clothianidin, imidacloprid and carbaryl on the lifespan and health of honey bees, workers were orally and topically exposed to LD5 doses of these insecticides. The survivorship of treated bees was monitored and the expression of three immune-related genes, hymenoptaecin (AmHym), bask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…Johnson and Carey [ 31 ] and Margotta et al [ 32 ] suggested that, due to the oxidative stress caused by the foraging environment and working flight muscles, the most active ADSs should be in the foragers, but this was not the case in our 20-day-old workers exposed to ID, as their more active ADSs were seriously suppressed (H2). Due to impairment of the ADS by ID, longevity [ 3 , 11 ], resistance to parasitoses [ 13 , 34 ], and harmful xenobiotics [ 35 ] may also be decreased in the foragers. Thus, decreased forager ADSs due to decreasing colony survival may impact the colony’s fitness (compare Lemanski et al [ 10 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and Carey [ 31 ] and Margotta et al [ 32 ] suggested that, due to the oxidative stress caused by the foraging environment and working flight muscles, the most active ADSs should be in the foragers, but this was not the case in our 20-day-old workers exposed to ID, as their more active ADSs were seriously suppressed (H2). Due to impairment of the ADS by ID, longevity [ 3 , 11 ], resistance to parasitoses [ 13 , 34 ], and harmful xenobiotics [ 35 ] may also be decreased in the foragers. Thus, decreased forager ADSs due to decreasing colony survival may impact the colony’s fitness (compare Lemanski et al [ 10 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that sublethal concentration of pesticides would cause transcriptional alterations involved in immune and detoxification functions in bee species [ 46 , 47 ]. The response of detoxification-related genes (such as cytochrome P450) and antimicrobial peptides [ 21 ] to chemical stress is very important for the development and survival of the host.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, neonicotinoids can affect a variety of genes of honeybees with different functions, such as immunity, detoxification and neural related genes [ 18 , 19 , 20 ]. Because neonicotinoids act as neurotoxins, it is not surprising that acetylcholinesterase (AChE) levels increase in bees exposed to corn fields treated with neonicotinoids [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, clothianidin, imidacloprid and thiamethoxam increased nAChRα expression when bees were treated in the laboratory after 72 h of treatment [ 18 ]. Cytochrome P450 enzyme expression level, which is associated with detoxification, has also been shown to be increased when bees are exposed to neonicotinoids [ 19 ]. The expression of immune-related genes can be suppressed as well by neonicotinoids, possibly promoting the establishment and replication viruses [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%